The sandbodys of shallow water delta during lake transgression under greenhouse climate and its reservoir property: a case study of the lower Jurassic in the Sichuan Basin, China - Shen, Qiuyuan; Long, Hui; Jiang, Lin; Yang, Yue; Liu, Tian; Geng, Chao; Peng, Jiayu; Li, Chenghai; Fu, Meiyan (Frontiers in Earth Science, 2025)
During the early Jurassic, arid and thermally intense greenhouse climate conditions led to dominantly oxidizing environments, resulting in the widespread development of purple-red mudstone. However, under this climatic backdrop, a lacustrine transgression occurred in the Sichuan Basin, China, leading to the formation of a distinctive lithological assemblage comprising purple-red mudstone interbedded with grey sandstone. The sedimentary facies and origin of sandbodies from this period remain insufficiently understood. This study focuses on the Zhenzhuchong Member of the Lower Jurassic Ziliujing Formation in the Guanyin–Data area, located in the southern Sichuan Basin. Due to the absence of drilling cores, samples were collected from four field outcrop sections. A combination of lithological description, petrographic identification, cathodoluminescence measurement, geochemical profiling, X-ray diffraction were employed to interpret the depositional environment of the Zhenzhuchong Member. The results reveal that the Zhenzhuchong Member is primarily composed of lithic quartz sandstones, with quartz content ranging from 80.7% to 93.4%. Geochemical proxies (e.g., Sr/Cu, Sr/Ba, Ni/Co ratios) indicate a warm to hot, freshwater-influenced, oxic setting. Sedimentary structures and stratigraphic sequences suggest deposition in a delta front to shallow lacustrine environment, including features such as distributary channels, mouth bars, shallow lake deposits. With ongoing lake transgression, distributary channels gradually retreated, giving way to an expansion of shallow lacustrine conditions. Sedimentation patterns during this phase were mainly driven by localized variations in water level. The characteristics purple-red coloration of mudstone is attributed to oxidizing conditions under the prevailing greenhouse climate. Subsurface data from well logs and seismic interpretation identify three sandbody units, with the 1# and 2# sandbodies displaying good lateral continuity, with branch shape. Favorable hydrocarbon shows within these sandstones suggest promising potential for natural gas exploration.